Numerical Implementation of a Hydro-Mechanical Coupling Constitutive Model for Unsaturated Soil Considering the Effect of Micro-Pore Structure - Cai, Guoqing; Han, Bowen; Li, Mengzi; Di, Kenan; Liu, Yi; Li, Jian; Wu, Tianchi (Applied sciences, 2021)
An unsaturated soil constitutive model considering the influence of microscopic pore structure can more accurately describe the hydraulic–mechanical behavior of unsaturated soil, but its numerical implementation is more complicated. Based on the fully implicit Euler backward integration algorithm, the ABAQUS software is used to develop the established hydro-mechanical coupling constitutive model for unsaturated soil, considering the influence of micro-pore structure, and a new User-defined Material Mechanical Behavior (UMAT) subroutine is established to realize the numerical application of the proposed model. The developed numerical program is used to simulate the drying/wetting cycle process of the standard triaxial specimen. The simulation results are basically consistent with those calculated by the Fortran program, which verifies the rationality of the developed numerical program.